A world of paper : Louis XIV, Colbert de Torcy, and the rise of the information state - Rule, John C.; Trotter, Ben S., 1949- (McGill-Queen's University Press, 2014)
Historians and social scientists have long identified bureaucracy as the modern state's foundation and the reign of France's Louis XIV as a model for its development. This book offers a fresh interpretation of bureaucracy through a close examination of the department of the Sun King's last foreign secretary, Jean-Baptiste Colbert de Torcy.